DEVELOPING LEARNING MEDIA BASED ADOBE FLASH CS.3 WITH CONTEXTUAL ON POLYHEDRON SUBJECT MATTER FOR STUDENT IN CLASS VIII OF SMP/MTs - Shafira Rahmatika Farid; Widayati Widayati (Universitas Ahmad Dahlan, 2018)
Mathematics learning media in the learning process can help students understand mathematics, but in fact, learning media availability is still limited. This study aims to develop learning media using Adobe Flash CS.3 with a contextual approach on subject matter Polyhedron for students of SMP/MTs VIII grade that eligible to use in the mathematics learning process. This study included research and development using the ADDIE method that consists of five stages: analysis, design, development, implementation, and evaluation. Subjects were subject matter experts, media experts, and students of Muhammadiyah Junior High School (SMP Muhammadiyah) 4 Yogyakarta and State Junior High School (SMP Negeri) 1 Gamping. Data were analyzed using qualitative analysis were converted into a cumulative grade Likert scale—data collection techniques, such as interviews, questionnaires, and observations. The product media developed has been assessed and validated by three experts, math learning materials, and three math learning media experts. The results of the expert assessment of the material obtained a score of 68 on average with a very good category. The results of expert media assessment obtained an average score of 105 with a very good category. The students 'responses to the technical quality assessed in the small-scale trials obtained an average score of 47.05 with both categories. The students' response to the technical quality assessed in the classroom usage test scored an average of 50.3 with either category. When viewed from the material experts and the media experts into the category, the feasibility level of the learning media of mathematics is very good, whereas when viewed from the student response on small-scale testing and trial class usage into the category of good. So that learning media developed feasible to use in learning mathematics.